Kambiyo senetlerinin zıyaı ve iptali - Utkan Mersin, Bilge (My University, 2024)
Bir kıymetli evrak türü olan kambiyo senetleri kıymetli evraka ilişkin hüküm ve koşullara tabidir. Türk Ticaret Kanununun 651 hükmü uyarınca kıymetli evrak zayi olduğu veya zıyaın ortaya çıktığı anda senet üzerindeki hak sahibi, mahkemeye başvurarak senedin iptaline karar verilmesini isteyebilir. Kambiyo senetlerinin zayi olması durumunda ise TTK m. 757 ve devamı hükümleri uyarınca senet iptal edilebilir. Bu çalışmada, kambiyo senetlerinin iptaline ilişkin hükümler, öğreti ve yargı kararlarındaki görüşler çerçevesinde değerlendirilecek; teoride ve uygulamada ortaya çıkardığı sorunlar incelenecektir.

Bills of exchange, which are a type of negotiable instruments, are subject to the terms and conditions of negotiable instruments. In accordance with the article 651 of the Turkish Commercial Code (“TCC”), if a negotiable instrument is lost, the rightful owner of the negotiable instrument may apply to the court, and request the cancellation of the negotiable instrument. If a bill of exchange is lost, the bill of exchange can be canceled in accordance with the article 757 and the subsequent provisions of TCC. In this study, the provisions regarding the cancellation of bills of exchange will be evaluated within the framework of doctrine and opinions in judicial decisions. The legal issues caused by these provisions in theory and practice will be examined.
Loss and cancellation of bills of exchange
Keywords: Bills of exchange; Foreign exchange; Kambiyo; Kambiyo senetleri; Kıymetli evrak; Law and legislation; loss; loss and cancellation; Negotiable instruments; Turkey; Türkiye; Yasa ve yasama; zayi olma; zıya ve iptal Negotiable instruments